Fecal Calprotectin Levels Dynamics in Newborns with High-Risk of Necrotizing Enterocolitis - Anna F. Pupysheva; Ekaterina I. Savelyeva; Valentina V. Piskunova; Anna A. Lenyushkina; Irina V. Nikitina; Olga D. Goncharuk; Olga A. Krogh-Jensen (Педиатрическая фармакология)
Background. Necrotizing enterocolitis (NEC) is severe gastrointestinal disease in newborns, its early clinical symptoms are nonspecific. Fecal сalprotectin (Cp) is considered as one of the early biomarkers of NEC, thus, its use in newborns is poorly known.Objective. The aim of the study is to evaluate clinical significance of fecal Cp measuring as an early NEC marker in newborns. Methods. The prospective cohort observational study included high-risk newborns (gestational age (GA) ˂ 33 weeks and/or body weight ˂ 1500 g) and moderate risk newborns (GV≥ 33 weeks at suspicion on NEC) of NEC admitted to the neonatal intensive care unit on the 1st day of life. The Cp level was studied via immune colorimetric method on the 3rd and 7th days of life in high-risk children and in all children at NEC manifestation. All patients were divided into 2 main subgroups after the end of the follow-up period: newborns with developed NEC (a) and children without NEC (b). Obtained Cp values were compared between these subgroups.Results. There were no statistically significant differences in Cp levels at the 3rd and 7th days of life in the high-risk group of children with NEC and without NEC. However, it was noted that children without NEC showed a decrease in Cp levels on the 7th day, while children with NEC manifestation, indeed, had increased levels. Cp levels did not differ in the moderate risk group.Conclusion. Single measurement of Cp level in newborns of any GA is uninformative towards the NEC prognosis and diagnosis. However, evaluation of the Cp level dynamics at the 7th day of life compared to the 3rd day of life may be considered as a promising non-invasive method for prognosis of NEC manifestation in premature infants (GA<33 weeks).